2017
DOI: 10.1111/1475-6765.12235
|View full text |Cite
|
Sign up to set email alerts
|

Simple politics for the people? Complexity in campaign messages and political knowledge

Abstract: Which parties use simple language in their campaign messages, and do simple campaign messages resonate with voters’ information about parties? This study introduces a novel link between the language applied during election campaigns and citizens’ ability to position parties in the ideological space. To this end, how complexity of campaign messages varies across parties as well as how it affects voters’ knowledge about party positions is investigated. Theoretically, it is suggested that populist parties are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 61 publications
8
90
1
1
Order By: Relevance
“…These effect sizes are thus generally small. But this is in line with the political psychology literature that studies the association between ideology language use of politicians and other elites [9,10,12]. Fig 2a thus provides consistent evidence that the link between ideology and language complexity exists across countries; where speech complexity appears to be increasing over time.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These effect sizes are thus generally small. But this is in line with the political psychology literature that studies the association between ideology language use of politicians and other elites [9,10,12]. Fig 2a thus provides consistent evidence that the link between ideology and language complexity exists across countries; where speech complexity appears to be increasing over time.…”
Section: Resultssupporting
confidence: 83%
“…Conservative political bloggers use less complex language than their liberal counterparts [10] and conservative citizens use language that scores lower on integrative complexity than liberal citizens [11]. The only study outside of the AngloSaxon context finds that politicians from the Alternative for Germany-a populist, culturally conservative party-use simpler language than mainstream politicians [12].…”
Section: Ideological Differences In Complexitymentioning
confidence: 95%
“…During the nineteenth century, extension of the franchise in the United Kingdom led frontbenchers to appeal to new voters through simpler parliamentary rhetoric (Spirling ). Currently, members of populist parties use simpler language in both campaigns and in parliament (Bischof and Senninger ; Brosius et al. ).…”
Section: Rebellion and Parliamentary Debatementioning
confidence: 99%
“…Recent studies have argued, for example, that simpler language is associated with the expansion of the franchise in the 19th United Kingdom, as cabinet ministers, in particular, attempted to make themselves comprehensible to new voters (Spirling ). Others have demonstrated that populist politicians use less complex language to distinguish themselves from other politicians and to reach voters (Bischof and Senninger ; Brosius et al ; Lin and Osnabrügge ). And, of course, much literature in the American context suggests that the tone and rhetoric of politics and campaigns can impact voter engagement and turnout (e.g., Ansolabehere and Iyengar ; Lau and Pomper ).…”
mentioning
confidence: 99%
“…Sentiment analysis can assess the level and direction of emotional arousal in a text, as well as the presence of specific discrete emotions (usually: anger, disgust, fear, joy, sadness, surprise). Much of this work is based on dictionaries, such as the Affective Norms for English Words (ANEW) (Bradley Hermann (1980Hermann ( , 2002 Complexity is another feature of text that is occasionally analyzed in political science (Hermann 2002;Thoemmes and Conway III 2007;Tetlock 1981;Conway et al 2014;Bischof and Senninger 2017). In its most basic form, complexity is measured as the number of words per sentence, and the length of the words in the sentences.…”
Section: A Text As Data Applicationsmentioning
confidence: 99%